2005
DOI: 10.1080/14015430500256592
|View full text |Cite
|
Sign up to set email alerts
|

Voice after supracricoid laryngectomy: Subjective, objective and self-assessment data

Abstract: Supracricoid laryngectomy (SCL) is an efficient surgical procedure for the treatment of selected laryngeal carcinoma, presently being performed not only in Europe but also in North America. The functional goals of the technique are voice and swallowing without a permanent tracheostoma. Perceptual and acoustic voice characteristics after SCL have been reported by different authors, but self-assessment data together with subjective and objective data have only been reported for a small number of subjects. Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
2
14
0
1
Order By: Relevance
“…Schindler et al, 2005Schindler et al, , 2006. In fact, it has been suggested that as long as the patient has a functional voice for verbal communication, QoL may return to near-normal (Schindler et al, 2005). However, that conclusion was based on results obtained using the VHI which, again, was not developed specifically for patients with laryngeal cancer and, when compared to the SECEL, has been shown to not be as sensitive to communication dysfunction (Johansson et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Schindler et al, 2005Schindler et al, , 2006. In fact, it has been suggested that as long as the patient has a functional voice for verbal communication, QoL may return to near-normal (Schindler et al, 2005). However, that conclusion was based on results obtained using the VHI which, again, was not developed specifically for patients with laryngeal cancer and, when compared to the SECEL, has been shown to not be as sensitive to communication dysfunction (Johansson et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…Although numerous studies have reported a severely dysphonic voice following supracricoid laryngectomy, these studies have also shown that patients only report few or moderate problems with concern to QoL (e.g. Schindler et al, 2005Schindler et al, , 2006. In fact, it has been suggested that as long as the patient has a functional voice for verbal communication, QoL may return to near-normal (Schindler et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Although the neoglottic mechanism for swallowing and generating voice after SCPL more closely resembles the physiology of the normal larynx than that in patients after total laryngectomy, function is not normal. There is evidence that these patients have chronic problem with swallowing and aspiration, and a perceptually abnormal voice with a breathy, strained, and rough quality . Much of these data come from large case series in Europe where this procedure is performed more commonly.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that these patients have chronic problem with swallowing and aspiration, [5][6][7] and a perceptually abnormal voice with a breathy, strained, and rough quality. 8,9 Much of these data come from large case series in Europe where this procedure is performed more commonly. Functional data after SCPL in the United States is much more limited, consisting of smaller series and shorter follow-up times, although excellent voice and swallowing results have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…methods (cricohyoidopexy=CHP, cricohyoi-doepiglottopexy= CHEP) based on whether the epiglottis is preserved or not. 1,2 Voice always gets modified after SCPL operation. The degree of dysphonia could significantly vary between different patients.…”
mentioning
confidence: 99%